Arsenic Contamination of the Coastal Aquifers in the North Coast of Java, Indonesia - Chrisna Adhi Suryono; Agus Sabdono; Bhaskoro Rochaddi; B. Tyas Susanti (Marine Science Department Diponegoro University, 2008)
A study was conducted to assess the Arsenic (As) metal contamination of the shallow aquifers in Jakarta, Semarang, and Surabaya city of Java and its relation to the highly developed industrial and domestic activities in the coastal region. Arsen was assayed in the waters of 30 wheals throughout the terrestrial cities, in residential zones using Atomic Absorption Spectrophotometer technique. The mean and standard deviation of As in Jakarta, Semarang and Surabaya were 17.19± 19.08, 1.78 ±2.28 and 0.59 ± 0.26 μgL-1, respectively.The r As concentration of groundwate shows in correlation with Fe significantly. The levels of As in some investigated three Indonesian metropolis cities were below the maximum allowable concentrations of metals recommended by Indonesian Drinking &. Domestic Water Quality Standard for Ground Water and WHO's (World Health Organization) Guideline Values for Drinking Wate, except for station 6 of Jakarta were concentration 59,65 μgL-1